Pengaruh Motivasi Wisatawan, Kualitas Layanan dan Persepsi Nilai terhadap Kepuasan Wisatawan (Studi Pada Wisatawan Domestik Di Kota Palembang) - Ummasyroh, Ummasyroh; Bustan, Jusmawi; Hamid, Abd (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This study aims to examine the causality relationship between the motivation of tourists, the quality of service and the perception of value to the satisfaction of tourists. The population in this study are tourists who have visited in 4 attractions in the city of Palembang namely: Jaka Baring Sport City, Kemaro Island, Kuto Besak Fort and Kambang Iwak Park. The method of analysis used in this study is path analysis, To meet the minimum requirements of path analysis tool, the sample of the research is 180 respondents. The type of sampling used is purposive sampling. The results showed that there was no significant influence on the motivation of tourists to satisfy tourists. There is a significant influence on the quality of service to the satisfaction of tourists. There is a significant influence on the perception of value to the satisfaction of tourists.